2018
DOI: 10.17159/2078-5151/2018/v56n2a2392
|View full text |Cite
|
Sign up to set email alerts
|

Open versus laparoscopic appendicectomy in acute appendicitis: results of a District General Hospital

Abstract: Background: Despite multiple studies comparing the two methods, the real advantages of laparoscopic appendicectomy (LA) compared to open appendicectomy (OA) are still unclear. Purpose of the current study was to compare the results between the two techniques in a district general hospital. Methods: The electronic records of all patients who underwent OA or LA in a one year period were reviewed retrospectively. The comparative data points assessed included age, gender, overall complications, length of stay and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…While in the study of Mitsugi Shimoda [17] reported male to female ratio are 1:1.6 in OA group and 1:1.4 in LA group. Whike in an other study D Zosimas [18] conducted in 2018 and reported male to female ratio is 1:1.06 which is almost same as in present study.…”
Section: Ao: Open Appendicectomy Group La: Laparoscopic Appendicectom...supporting
confidence: 88%
“…While in the study of Mitsugi Shimoda [17] reported male to female ratio are 1:1.6 in OA group and 1:1.4 in LA group. Whike in an other study D Zosimas [18] conducted in 2018 and reported male to female ratio is 1:1.06 which is almost same as in present study.…”
Section: Ao: Open Appendicectomy Group La: Laparoscopic Appendicectom...supporting
confidence: 88%
“…In contrast, in another similar retrospective study conducted by Fujishiro et al (28) on 4,489 pediatric patients underwent appendectomy, 70.5% of them were laparoscopic surgery, they found that the incidence of postoperative complications and length of hospitalization of patients with LA are similar to those of open appendectomy for acute appendicitis (28) . In 2018, Zosimas and colleagues reviewed the electronic records of 300 patients underwent either OA (166) or LA (134) in a one-year retrospective period, they concluded that although the LA approach surgery is safe and effective, but the choice between open traditional appendectomy and laparoscopic surgery should be tailored according to the clinical scenarios and the preference of the surgeons (29) .…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis of perforated appendicitis is closely related to incision infection, postoperative recurrence and complete surgical resection (16). Research shows that the incision infection rate of patients after laparoscopic intervention for appendicitis is significantly lower than that of open surgery (17). For example, in the studies by Zwintscher NP et al (18), laparoscopic appendectomy for children with perforated appendicitis has a lower incidence of postoperative complications and shorter length of stay.…”
Section: Discussionmentioning
confidence: 99%